ChemInform Abstract: Metal‐Free Intramolecular Transannulation of N, 3‐Diaryloxirane‐2‐carboxamides: A Concise and Versatile Route to 3‐Arylquinolin‐2(1H)‐ones. Issue 34 (August 2015) - Mamedov, Vakhid A.; Mamedova, Vera L.; Kadyrova, Saniya F.; Khikmatova, Gul'naz Z.; Gubaidullin, Aidar T.; Rizvanov, Il'dar Kh.; Latypov, Shamil K.
Abstract The intramolecular transannulation of trans‐epoxides (III) towards quinolinones (IV) proceeds via a Meinwald rearrangement and Friedel—Crafts alkylation processes, featuring an exclusive 1, 2‐aryl migration.